2016
DOI: 10.1371/journal.pone.0164142
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Exposure to Globally Relevant Zoonotic Parasites in the Estonian Population

Abstract: We investigated Estonian population and its selected subgroups for serological evidence of exposure to Ascaris lumbricoides, Echinococcus spp., Taenia solium, Toxocara canis, Toxoplasma gondii, and Trichinella spiralis. Serum samples from 999 adults representing general population, 248 children aged 14–18, 158 veterinarians, 375 animal caretakers, and 144 hunters were tested for specific immunoglobulin G antibodies against the selected parasites using commercial enzyme immunoassays (ELISA). Sera yielding posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 35 publications
3
34
1
Order By: Relevance
“…13 However, zoonotic exposure is not uncommon through exposure to parasites of livestock and companion animals. [14][15][16] Indeed, a number of relatively recent studies have identified Ascaris suum infection and associated pathology (such as Loffler syndrome) to occur (albeit at low levels) in northern European and North American pig farming areas. [17][18][19][20] A more common cause of zoonotic helminth infections comes from Toxocara canis and T. cati which naturally infect dogs and cats.…”
mentioning
confidence: 99%
“…13 However, zoonotic exposure is not uncommon through exposure to parasites of livestock and companion animals. [14][15][16] Indeed, a number of relatively recent studies have identified Ascaris suum infection and associated pathology (such as Loffler syndrome) to occur (albeit at low levels) in northern European and North American pig farming areas. [17][18][19][20] A more common cause of zoonotic helminth infections comes from Toxocara canis and T. cati which naturally infect dogs and cats.…”
mentioning
confidence: 99%
“…Used on rodent hosts, these methods deduced a 14.2% T. canis seroprevalence and showed ELISA to be more sensitive than PCR for detecting infection with the parasite (Krucken et al 2017). Studies using immunodiagnostic methods have been carried out worldwide (Krucken et al 2017;Li et al 2017;Lassen et al 2016;Klockiewicz et al 2019a). Serological analysis also allows the easy detection of mixed infections in hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Both echinococcosis and toxocarosis can be diagnosed with ELISA and Western blot. The use of serological data to study infection in wildlife is widely accepted (Fillaux and Magnaval 2013;Lassen et al 2016;Pagnozzi et al 2016). Seroprevalence studies of infected wild animals can be a good, easy, and cheap way to determine the occurrence of these zoonotic parasites in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In the northernmost Baltic country Estonia, as part of a larger study on zoonotic parasitic infections, 1 (0.7%, 95% CI 0.0-3.4) of 144 hunters tested seropositive for Echinococcus spp. using a commercial ELISA (Lassen et al 2016). In particular, hunters might be more exposed to Echinococcus canadensis (Oksanen andLavikainen 2015, Romig et al 2015).…”
Section: Discussionmentioning
confidence: 99%